Research Note: Heterosis for egg production and oviposition pattern in reciprocal crossbreeds of indigenous and elite laying chickens - Yuanmei Wang; Yanyan Sun; Aixin Ni; Yunlei Li; Jingwei Yuan; Hui Ma; Panlin Wang; Lei Shi; Yunhe Zong; Jinmeng Zhao; Shixiong Bian; Jilan Chen (Poultry Science, 2022)
Heterosis has been widely utilized in chicken breeding to improve economically important traits. However, few studies focused on revealing the factors contributing to egg production heterosis. In this study, White Leghorn and Beijing-You chickens were used as parental breeds to generate purebreds (WW, YY) and reciprocal crossbreeds (WY, YW) to characterize heterosis for egg production traits including age at first egg (AFE), clutch traits, oviposition pattern, and egg quality traits. Results showed that egg number until 35 wk of age (EN35) was higher in crossbreeds than the average of purebreds (P < 0.05) and exhibited positive heterosis of 4.03% and 2.84%) in WY and YW respectively. Crossbreeds commenced laying earlier than the average of purebreds (P < 0.05) with negative heterosis of −1.24% and −0.92% for WY and YW respectively. Moreover, EN35 had negative correlation with AFE (r = −0.85) and positive correlation with average clutch length (ACL) (r = 0.48) and maximum clutch length (MCL) (r = 0.66). However, negative heterosis for ACL (−19.62%, −16.51%) and MCL (−22.88%, −18.97%) were obtained in WY and YW, respectively. This may be due to the positive heterosis for number of pauses, which was highly correlated with ACL (r = −0.68) and MCL (r = −0.74). The crossbreeding improved the oviposition pattern. Percent egg laying that occurs between 7:00 and 14:00 was 91.50% (WW), 68.28% (YY), 76.87% (WY), and 79.68% (YW) in the experimental populations. On the other hand, oviposition interval (OI) had negative heterosis in crossbreeds and was negatively correlated with EN35 (r = −0.60). Positive heterosis for egg weight of 2.63% and 3.94% and yolk weight of 4.74% and 6.07% were observed in WY and YW, respectively. Taken together, egg production related traits did not contribute equally to EN heterosis. The AFE and OI exhibited significant correlation with EN indicating that they would be important drivers for EN heterosis.